The moderating effect of bilateral investment treaty stringency on the relationship between political instability and subsidiary ownership choice. Issue 1 (February 2017) - Williams, Christopher; Lukoianova (Vashchilko), Tatiana; Martinez, Candace A.
Highlights: We study the moderating effect of bilateral investment treaty (BIT) stringency. It moderates the link between political instability and subsidiary ownership choice. We analyze 289 investments made by AEX-listed MNEs in 34 countries in 2004–2013. As instability increases, importance of BIT stringency for majority ownership rises. Robustness tests using other risk indicators provide support to our hypothesis. Abstract: We investigate whether the degree to which a bilateral investment treaty (BIT) protects against expropriation (i.e., its "stringency") influences the international strategy of multinational enterprises (MNEs) as they invest in countries with varying levels of political instability. We draw on institutional logic and insights from political economics to hypothesize that BIT stringency will moderate the established positive relationship between host country political instability and minority ownership. Analysis of a sample of 289 foreign investments made by AEX-listed Dutch MNEs in 34 countries between 2004 and 2013 provides support: a more stringent BIT will encourage the MNE to choose a majority stake as political instability rises. Robustness tests provide further support for our argument. The results have both managerial and policy implications relating to the role that BIT stringency plays in determining MNE strategy.